2019
DOI: 10.1002/aqc.3112
|View full text |Cite
|
Sign up to set email alerts
|

Do active‐dispersing insects dominate the invertebrate fauna of rock pools in the wet–dry tropics, Kimberley, Australia?

Abstract: Invertebrate assemblages of tropical freshwater rock pools (FRPs) are poorly known compared with temperate regions, where FRPs contain specialized, endemic taxa of high conservation value. Invertebrates were sampled from pristine FRPs in the Morgan River catchment in the Australian wet–dry tropics in the 2015 and 2016 wet seasons. Taxa were classified as either active or passive dispersers and by functional feeding groups. A range of physical variables were examined to identify associations with invertebrate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Moreover, tropical rainfall conditions allow longer inundations that enable predators with longer aquatic life cycles to breed in the rock pools. For instance, in a similar climate to the present study (the wet-dry tropics), Carey et al (2019) found that ±60% of the taxa in sandstone rock pools were predators in Kimberley, Australia. However, as the researchers used a large mesh size during sampling, it is possible that they overestimated the relative diversity of predators because many smaller filter feeders and collectors will have been missed during sampling.…”
Section: Tree Holessupporting
confidence: 79%
“…Moreover, tropical rainfall conditions allow longer inundations that enable predators with longer aquatic life cycles to breed in the rock pools. For instance, in a similar climate to the present study (the wet-dry tropics), Carey et al (2019) found that ±60% of the taxa in sandstone rock pools were predators in Kimberley, Australia. However, as the researchers used a large mesh size during sampling, it is possible that they overestimated the relative diversity of predators because many smaller filter feeders and collectors will have been missed during sampling.…”
Section: Tree Holessupporting
confidence: 79%
“…Rock pools in Australia, Botswana, and South Africa tend to be inhabited by one or two species (Brendonck et al, 2015; Jocqué et al, 2006). Exceptionally five, six, seven, and eight species were found in rock pool clusters from northwestern Australia (Carey, Cross, et al, 2019), south‐western Australia (Pinder et al, 2000), Côte d'Ivoire (Snoeks et al, 2021), and Utah (USA) (Baron et al, 1998). The most likely explanations for the large number of odonates we found include neotropical latitude and humidity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a granite outcrop can house a highly heterogeneous set of freshwater habitats inhabited by a large diversity of invertebrates with different ecological requirements. Community analyses of tropical rock pools are rare (but see Carey, Cross, et al, 2019;Jocqué et al, 2010;Snoeks et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation